Three essays on dishonesty and corruption (2019)
"This dissertation is made of three essays. In each of them, I present a study related to dishonest conducts that economic agents can develop in the contexts of public administration, business, or academic environments. Through behavioral and experimental tools, I evaluated the incidence of some factors, such as a variation in the economic environment, personal traits, and weak institutions, on the occurrence of dishonest acts. Also, I evaluated the effectiveness of some institutions to discourage opportunistic behaviors when managing public funds. In Chapter 1, with Juan Camilo Cárdenas, we study whether individuals who are interested in initiating a business in Colombia where dishonest practices are perceived as common in business are ethically different from those who prefer other career paths. We evaluated differences in the level of acceptance of rule-breaking in civil and academic contexts?among undergraduates with entrepreneurship preferences and non-entrepreneurship preferences. Also, we evaluated the seriousness that they linked to different kinds of transgressions. In Chapter 2, I study, through a laboratory experiment, how voluntary contributions to finance the production of a good distributed by a state agent evolve in a context of weak accountability. Also, I evaluate the effects of three institutions, based on binding and non-binding communication rather than pecuniary punishments to promote contributions and reduce misappropriation, within this scenario of weak accountability. In Chapter 3, I experimentally address whether a sudden increase of State resources, around those who can potentially assign them improperly or capture them privately, increases the likelihood of economic agents to behave corruptly. The findings of this dissertation contribute to improve our understanding of the occurrence and persistence of dishonest acts. Furthermore, they contribute to the design of policies to discourage dishonest and corrupt behaviors."--Tomado del Formato de Documento de Grado.